DETERMINAN KINERJA KEUANGAN BPR SYARIAH DI JAWA TENGAH : EFEK MODERASI NON-PERFORMING FINANCING - Agung Prayogi; Zella Arfi Andiny; Yoka Lestari; Annastasya Nur Salsabilla; Meilia Trivanti (Jurnal Ekonomi Bisnis dan Kewirausahaan, 2025)
This study aims to analyze the effect of murabahah, ijarah multijasa, mudharabah, and musyarakah financing on the financial performance of Islamic Rural Banks (BPR Sharia) in Central Java, with Non-Performing Financing (NPF) as a moderating variable. The research was conducted on 11 BPR Sharia from a total population of 28 using purposive sampling. The data used were quarterly financial reports for the period 2022–2024. Analytical methods include descriptive statistics, classical assumption tests, multiple linear regression, and Moderated Regression Analysis (MRA). The results indicate that musyarakah financing has a significant positive effect on financial performance, while murabahah financing has a significant negative effect. Meanwhile, ijarah multijasa and mudharabah financing have no significant effect. Furthermore, NPF moderates the relationship between murabahah and mudharabah financing on financial performance but is not significant for ijarah and musyarakah. These findings offer valuable implications for BPRS management in optimizing appropriate financing types and managing credit risk to enhance financial performance..